A versatile system for the neuronal subtype specific expression of lentiviral vectors - Tolu, Stefania; Avale, M. Elena; Nakatani, Hiroko; Pons, Stephanie; Parnaudeau, Sebastien; Tronche, Francois; Vogt, Angelika; Monyer, Hannah; Vogel, Roland; Chaumont, Fabrice de; Olivo-Marín, Jean-Christophe; Changeux, Jean-Pierre; et al. (The FASEB journal, 2010)
Lentiviral expression vectors are powerful tools for gene therapy and long-term gene expression/repression in the mammalian brain. However, no specificity of transduction has been reported so far in the central nervous system. Here we have developed a novel system to achieve a neuronal subtype specific expression in either dopaminergic (DA) or GABAergic neurons. We employed a delivery strategy by which the transgene is not expressed until its activation by Cre recombinase. We successfully tested the system in vitro and then used this novel lentivector, containing loxP sites, in 2 different transgenic mouse lines expressing Cre either in DA or in GABAergic neurons. In both lines the reporter gene was detected exclusively in Cre-positive cells, demonstrating that with this experimental approach we were able to achieve completely specific expression of transgenes delivered by lentiviral vectors. This universal system can be applied to all neural subtypes making use of the growing number of specific Cre driver lines.—Tolu, S., Avale, M. E., Nakatani, H., Pons, S., Parnaudeau, S., Tronche, F., Vogt, A., Monyer, H., Vogel, R., de Chaumont, F., Olivo-Marin, J.-C., Changeux, J.-P., Maskos, U. A versatile system for the neuronal subtype specific expression of lentiviral vectors. FASEB J. 24, 723-730 (2010). www.fasebj.org
Erstmals am 26 October 2009 online veröffentlicht
Gesehen am 28.11.2023